Étude socioterminologique du vocabulaire de l’esclavage pour la constitution d’un glossaire bilingue gungbe-français - Charles Dossou Ligan (Linguistik Online)
Sometimes, language codifies phenomena differently, depending on several parameters that need to be accommodated under social aspects. This work proposes a terminology of slavery based on certain common designations of acts and actors of slavery and the slave trade itself. The working method adopted consisted in exploring the language of the designations and searching for their equivalents or the etymology of the concepts. This involved describing the process of capturing, buying and selling, transporting and exploiting slaves, followed by the construction of a lexical field. It emerged that the terms that codify the slave or slavery in Gungbe vary in the social environment according to several parameters linked to the experience or perception of the speaker.